2017
DOI: 10.1073/pnas.1615715114
|View full text |Cite
|
Sign up to set email alerts
|

Gut dysbiosis breaks immunological tolerance toward the central nervous system during young adulthood

Abstract: Multiple sclerosis (MS) is an autoimmune disease targeting the central nervous system (CNS) mainly in young adults, and a breakage of immune tolerance to CNS self-antigens has been suggested to initiate CNS autoimmunity. Age and microbial infection are well-known factors involved in the development of autoimmune diseases, including MS. Recent studies have suggested that alterations in the gut microbiota, referred to as dysbiosis, are associated with MS. However, it is still largely unknown how gut dysbiosis af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 86 publications
(105 reference statements)
0
35
1
Order By: Relevance
“…Microbiome transplants from MS patients to mice have differential effects on subsequent susceptibility to EAE (Berer et al, ). Modulation of specific species of bacteria has a significant impact on the susceptibility to the development of EAE (Yadav et al, ); clinical trials are ongoing in MS.…”
Section: Comparison Of the Role Of Inflammation In Physiologic And Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiome transplants from MS patients to mice have differential effects on subsequent susceptibility to EAE (Berer et al, ). Modulation of specific species of bacteria has a significant impact on the susceptibility to the development of EAE (Yadav et al, ); clinical trials are ongoing in MS.…”
Section: Comparison Of the Role Of Inflammation In Physiologic And Pamentioning
confidence: 99%
“…Microbiome transplants from MS patients to mice have differential effects on subsequent susceptibility to EAE(Berer et al, 2017). Modulation of specific species of bacteria has a significant impact on the susceptibility to the development of EAE(Yadav et al, 2017); clinical trials are ongoing in MS.The above focus on the EAE model does not negate the utility of other animal or in vitro models in helping define the mechanisms of many of the individual components or processes that comprise the total picture of MS. Toxic and hypoxic/ischemic models may shed light on oligodendrocyte damage with consequent demyelination and remyelination, while there are many experimental manipulations which help us understand, for example, the breakdown of the BBB or astrogliosis.…”
mentioning
confidence: 99%
“…For example, imbalance of gut microbiota, referred to as dysbiosis, is associated with multiple sclerosis, a chronic demyelinating disease triggered by an autoimmune mechanism (Yadav et al 2017). Subgingival dysbiosis has been reported in patients with systemic lupus erythematosus, another autoimmune disease (Correa et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This system is connected to the central nervous system through hormonal or innate neuronal pathways [51] that are critical for its development and vice versa [52]. Furthermore, studies have shown that the gut flora is critically involved in immunoregulation [53][54][55], whereas some reports have shown the immune system as an important regulator of neurodevelopment and synaptic function in the brain [56]. In line with this, immune dysfunction and/or autoimmunity have been speculated to be associated with many neuropsychiatric and neurodevelopmental disorders, such as ADHD [57,58].…”
Section: Gut Microbiome Microbiota and Behaviormentioning
confidence: 99%